Fractional laser and laser assisted corticosteroid delivery for hypertrophic scars in thermal burns - Ni Putu Susari Widianingsih; Cita Rosita S. Prakoeswa (PAGEPress Publications, 2019)
The unprecedented survival of individuals who sustain acute burns and other trauma has increased the necessity for effective modalities in the treatment and rehabilitation of patients. Hypertrophic scars and contractures are common following thermal burns injury. Cutaneous scars can be complex and thus the approach to therapy is often multimodal with only moderate success. Intralesional corticosteroids have long been a main treatment of hypertrophic and restrictive scars. Recent advance in laser technology and applications now provide additional options for improvements in function, symptoms, and cosmesis. The ablative zones created by fractional ablative lasers may also be used in the immediate post-operative period to enhance delivery of drugs and other substances. This case report shows the successful use of fractional laser assisted corticosteroid to treat burn scars. It is need more extensive clinical trial to prove this method can be a therapeutic option for the extensive cutaneous scarring in burn patients.